2006
DOI: 10.1074/jbc.m604217200
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Residues Lys-19 and Lys-49 of β-Catenin Regulate Its Levels and Function in T Cell Factor Transcriptional Activation and Neoplastic Transformation

Abstract: Wnt signaling regulates cell fate determination, proliferation, and survival, among other processes. Certain Wnt ligands stabilize the ␤-catenin protein, leading to the ability of ␤-catenin to activate T cell factor-regulated genes. In the absence of Wnts, ␤-catenin is phosphorylated at defined serine and threonine residues in its amino (N) terminus. The phosphorylated ␤-catenin is recognized by a ␤-transducin repeat-containing protein (␤TrCP) and associated ubiquitin ligase components. The serine/threonine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 26 publications
4
55
0
Order By: Relevance
“…The activation of the SCF ␤-TrCP depends on the presence or absence of a Wnt ligand, whereas Siah-1-mediated ␤-catenin degradation is induced by activation of p53 during genotoxic stress. In the SCF ␤-TrCP complex, ␤-TrCP binds the phosphorylated N-terminal domain of ␤-catenin leading to the attachment of ubiquitin chains on Lys 19 and Lys 49 (47,48). Here, we show that Siah-1 binds the non-phosphorylated ␤-catenin, leading to the attachment of ubiquitin chains at the very C-terminal region of the (arm) domain on Lys 666 and Lys 671 .…”
Section: ␤-Catenin Ubiquitination By Siah-1 Protection By Tbl1mentioning
confidence: 81%
“…The activation of the SCF ␤-TrCP depends on the presence or absence of a Wnt ligand, whereas Siah-1-mediated ␤-catenin degradation is induced by activation of p53 during genotoxic stress. In the SCF ␤-TrCP complex, ␤-TrCP binds the phosphorylated N-terminal domain of ␤-catenin leading to the attachment of ubiquitin chains on Lys 19 and Lys 49 (47,48). Here, we show that Siah-1 binds the non-phosphorylated ␤-catenin, leading to the attachment of ubiquitin chains at the very C-terminal region of the (arm) domain on Lys 666 and Lys 671 .…”
Section: ␤-Catenin Ubiquitination By Siah-1 Protection By Tbl1mentioning
confidence: 81%
“…It has been shown that the K19/K49 double mutant form of ␤-catenin is stabilized as a result of reduced ␤TrCP-dependent ubiquitination (Winer et al, 2006). According to the above-mentioned results, it is possible that K19 and K49 of ␤-catenin are involved in regulating its stability by PCAF.…”
Section: K19 and K49 Of ␤-Catenin Are Important For Its Acetylation Amentioning
confidence: 93%
“…␤-Catenin is usually degraded by ubiquitin proteasome system, and Lys-19 and Lys-49 are important sites for ␤-catenin ubiquitination (Aberle et al, 1997;Winer et al, 2006). Single amino acid substitutions of either Lys-19 or Lys-49 of ␤-catenin slightly affect its ubiquitination, but the K19/K49 double mutant ␤-catenin is stabilized as a result of significant reduced ␤TrCP-dependent ubiquitination (Winer et al, 2006). These findings implied that other posttranslational modifications at Lys-19 and Lys-49, such as acetylation, might affect the ubiquitination and stability of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations